PEMANFAATAN E-TAILING UNTUK MENINGKATKAN PENJUALAN DAN DAYA SAING PADAUSAHA KECIL DAN MENENGAH - Yesni Malau (LPPM Universitas Bina Sarana Informatika, 2014)
Artificial intelligenceis apart ofcomputerscienceis widely usedbecause of its abilitytomimicthe humanway of thinking. Andthe concept ofe-tailing is asystem ofselling and buyingproducts, information, andservices performedbya computernetworkutilizingtheInternet. E-taling in the marketingof goodsneededin expandingoutreachmarketingto increasesalesand competitiveness ofsmall and medium enterprisesthat will increaserevenue forthe business, withpemnafaatne-tailing, the transaction can bedone anytimeand anywherewithoutanyrestrictionof time. Andthee-tailing marketing costswould be farmoreeffective thanconventional salesmeets allthe requirementsbyproviding consumers with theinformationandservice excellenceshouldbe the main focus, withthe sales of thesystemto implementthe e-tailing onsmall and medium enterprisesis a solutionthe righttoincrease salesandbusiness competitiveness.